Pengaruh Kompensasi Dan Tingginya Beban Kerja Terhadap Kepuasan Kerja Tenaga Kerja Kontrak Di PT. Socfindo Mata Pao - Siska Pertiwi; Hablil Ikhwana; Siti Wardah Pratidina Nasution (Public Service and Governance Journal, 2023)
The main goal of working human resources is to get compensation, but there are times when compensation and workload are often unequal. For this reason, this research was conducted, in order to find out how much influence compensation and workload have on workers' satisfaction, especially contract workers and other workers, who expect a daily salary, because the workers' compensation system is usually daily, and depends on how many jobs they get. carried out by the worker. This study uses a quantitative method with several tests namely reliability analysis, classical assumption deviation test, and linear regression. The t value of the compensation variable (X1) is -0.859, thus t count < t table, then Ho is accepted and H1 is rejected, which means that the compensation variable (X1) has no significant effect on employee job satisfaction. The t value of the workload variable (X2) is 1.116, thus t count <t table, then Ho is accepted and H1 is rejected which means that the workload variable (X2) has no significant effect on employee job satisfaction. In the Anovab table, the calculated F value is 0.656 while the F table value is 3.26. Thus F count < F table means that the compensation and workload variables have no significant effect on job satisfaction at PT. Socfindo Matapao. The coefficient of determination (R2) value of the regression result is 0.038 meaning that compensation and workload contribute to the influence on job satisfaction of employees of PT. Socfindo Matapao of 3.8% This result is the result of (R2 x 100%), while the remaining 86.2% is influenced by other variables not examined in this study.